Obtenção, caracterização e aplicação em alimentos de isolado e concentrado proteico de amêndoa de castanha de caju (Anacardium occidentale L.) - Lima, Larissa Vieira de (2018)
The cashew nut kernel (CNK) is the cashew tree product with the highest economic value; it is rich in proteins and polyunsaturated fatty acids. Among the by-products of cashew nut processing are the broken kernels, which are less valuable commercially. As a way of adding value to it, this study developed some processes to attain a protein concentrate and isolate from the CNK. Two rotational central composite designs (RCCD) were developed: the first one for the acid precipitation of proteins during concentration and the second one for alkaline protein solubilization, preliminary step to precipitation in obtaining protein isolate. The RCCD for protein acid precipitation was conducted with two independent variables: pH (3.0 a 4.5) and agitation time (15 to 120 minutes) in addition to a dependent variable: protein content. For protein solubilization, two independent variables were used: pH (8.0 a 12.0) and agitation time (15 to 180 minutes); also a dependent variable: protein content. A time of 15 minutes in the pH range from 4.0 to 4.5 has shown efficiency in regards of precipitation, obtaining a concentrate with 54.5% of protein, and a mass output of 76.7%. For the solubilization step, pH 10 with 15-minute agitation was more efficient and with following acid precipitation, an isolate with 86.2% of protein and mass output of 19.0% was obtained. The concentrate and the isolate have low solubility in aqueous medium in a pH close to 4.0; water absorption capability of 1.85 mL/g and 1.74 mL/g, and oil absorption capacity of 1.06 mL/g and 0.90 mL/g respectively. Proteins with this profile are more adequate to semi-solid foods. The CNK protein isolate is the only one that showed potential to form foam and could be applied in products that require aeration. The protein concentrate was used in vegetable hamburgers as a substitute for textured soy protein (TSP). The hamburgers made of TSP and protein concentrate went through sensory evaluation. An acceptability and intention to purchase test was conducted on 50 untrained tasters. No significant difference (p>0.05) was found in the hamburgers acceptability rate, and the ones formulated with protein concentrate received an average of 6.6 in a 9 point scale. With respect to intention to purchase, 60% of the tasters probably or certainly would buy the product. Therefore, the protein concentrate of CNK can be used in the preparation of vegetable burgers.